The Impaired Subcortical Pathway From Superior Colliculus to the Amygdala in Boys With Autism Spectrum Disorder - Huang, Yiting; Vangel, Mark; Chen, Helen; Eshel, Maya; Cheng, Ming; Lu, Tao; Kong, Jian (Frontiers in Integrative Neuroscience, 2022)
Objective Increasing evidence suggests that a subcortical pathway from the superior colliculus (SC) through pulvinar to the amygdala plays a crucial role in mediating non-conscious processing in response to emotional visual stimuli. Given the atypical eye gaze and response patterns to visual affective stimuli in autism, we examined the functional and white matter structural difference of the pathway in boys with autism spectrum disorder (ASD) and typically developing (TD) boys. Method 38 boys with ASD and 38 TD boys were included. We reconstructed the SC-pulvinar-amygdala pathway in boys with ASD and TD using tractography and conducted the analysis across tract-specific measurements to compare the white matter difference between the two groups. An ROI- based functional analysis was also applied among the key nodes of the pathway to explore the functional connection network. Results DTI analysis showed decreased fractional anisotropy (FA) of the pathway in boys with ASD compared to TD. The reduced FA is marginal related with the communication impairment in boys with ASD. In addition, compared to TD, we found that the ASD group was associated with an increased functional connectivity between the right pulvinar and the left SC. Conclusion Our results indicated that the functional and white matter microstructure of the subcortical route to the amygdala might be altered in individuals with autism. And this atypical structural change of the SC-pulvinar-amygdala pathway may be related to the atypical communication pattern in boys with ASD.